Adsorpsi Zat Organik Limbah Laundry Menggunakan Karbon Aktif dari Limbah Kulit Singkong (Manihot esculenta Crantz) - Mita Destanti; Rahmawati Rahmawati; Nirmala Sari; Fera Annisa; T. Andi Fadlly (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2025)
In this study, activated carbon from cassava peel waste has been synthesized, with the aim of analyzing its effectiveness in reducing BOD and COD levels in laundry wastewater. Activated carbon was synthesized through a carbonization process at various temperatures (250°C, 300°C, 350°C) for 1.5 hours, then chemically activated using 2% KOH and physically activated with microwaves. Morphological characterization using SEM, and adsorption effectiveness was tested with contact time variations of 0 and 5 days for BOD, COD, pH, and temperature parameters. The results of SEM characterization showed that the carbonization temperature of 300°C produced optimal micro and mesoporous pore structures without structural damage. Treatment with activated carbon from 300°C carbonization (sample A2) showed the best performance, with a decrease in BOD from 450 mg/L to 200 mg/L and COD from 21.7 mg/L to 3.72 mg/L. The pH and temperature values after adsorption also meet environmental quality standards, namely neutral pH (7) and temperature 25.7°C. Activated carbon from cassava peel waste has been proven to be effective as an environmentally friendly adsorbent for laundry waste processing.